Lead testing of children and homes: results of a national telephone survey. - Binder, Sue; Matte, Thomas D.; Kresnow, Marcie-jo (Public Health Reports)
A national random digit dial telephone survey was conducted to determine the lead screening rates for U.S. children and homes. The National Center for Injury Prevention and Control successfully contacted 5,238 households between April 28 and September 18, 1994. The results revealed that approximately 24 percent of children aged 0–6 years had been tested for lead. Higher rates of testing were documented for children living in homes built before 1960, those living in homes with low household income, those living in rental units, and those living in the Northeast. Only some 9 percent of U.S. housing units had been tested for lead paint; older houses were not more likely to have been tested than newer ones. Based on these data, it would seem that current approaches to lead poisoning prevention are not reaching the children that are most at risk.